Policy blind spots leave ~2 million displaced without protection in Burkina Faso - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
What happens when ~2 million people are forced to move, but the policies meant to support them don’t speak to each other? CGIAR Climate Security researchers reviewed 40+ Burkinabé national policies and international strategies to find out.